[updated and corrected from 2017] WEAI (Women's Empowerment in Agriculture Index) - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
WEAI was developed during Phase I from a project, led by IFPRI and part of the PIM portfolio. The stage was incorrectly entered in 2017 and is now considered stage 3.